Performance enhancement of a solar still using magnetic powder as an energy storage medium‐exergy and environmental analysis. Issue 8 (13th June 2022) - Dhivagar, Ramasamy; Shoeibi, Shahin; Kargarsharifabad, Hadi; Ahmadi, Mohammad Hossein; Sharifpur, Mohsen
Abstract: The use of different energy storage materials can have a high effect on the water productivity of solar desalination. This study evaluates the impact of magnetic powders on modified solar still (MPSS) performance and compares the results with conventional solar still (CSS). Black iron oxide magnetic powder was selected to increase solar radiation absorption. The black iron magnetic powder simultaneously acts as a thermal storage material and a porous absorber medium. The thermal energy stored in the magnetic powder improved the performance of the MPSS during peak solar irradiation hours, resulting in higher productivity. The results showed that the thermal performance of MPSS was higher than CSS. The MPSS exhibited a 39.8% higher evaporative and 14.5% higher convective heat transfer rate compared with CSS. Results showed that the cumulative water productivity of MPSS was 31.2% greater than CSS. Also, the energy and exergy efficiencies of MPSS were improved by 18.9% and 19.04%, respectively, compared with CSS. Moreover, the predicted payback period in MPSS and CSS were 3.2 and 4.3 months. Additionally, the CO2 reduction of MPSS was improved by approximately 45.53% compared with that of CSS. The results also showed that the exergoeconomic parameter of MPSS and CSS with energy base was equal to 33.1 and 24.56 kWh/, respectively. Abstract : The modified solar still (MPSS) and conventional solar still (CSS) were tested in identical climatic circumstances and the following conclusions were reached: The water temperature observed in MPSS was 11.9% higher than in CSS. Compared to CSS, the MPSS achieves higher evaporation and convection rates of 39.8% and 14.5%, respectively. The usage of magnetic powder in basin water has highly raised the cumulative productivity in MPSS to 31.2% more than CSS. The CO2 reduction of MPSS was improved by approximately 45.53% compared to CSS.